Підвищення ступеня карбонізації содо-бікарбонатних розчинів у содовому виробництві як спосіб мінімізації забруднення атмосфери вуглекислим газом - Порохня, Микола Федорович (Національний університет "Львівська політехніка", 2018)
The production of soda ash and refined sodium bicarbonate are one of the most studied chemical-technological processes. However, the solution of environmental problems for this type of industry is still an actual scientific task. One of the significant problems is the excessive emissions of carbon dioxide into the atmosphere. Therefore, the aim of this paper is the analysis ways of minimizing carbon dioxide emissions by intensification the main technological process.
Keywords: виробництво соди; содо-бікарбонатні розчини; карбонізація; забруднення атмосфери; вуглекислий газ; циліндричні апарати барботажного типу